The effect of purple mangosteen (Garcinia mangostana) peel extract on collagen fiber in male Wistar rats after Ultraviolet-B (UV-B) exposure - Tarvin Jit Singh Gill; I Gusti Ayu Dewi Ratnayanti; I Gusti Kamasan Nyoman Arijana (Intisari Sains Medis, 2018)
Background: Skin aging can be caused by long-term ultraviolet (UV) exposure that usually called as photoaging. Administered antioxidant substances can delay the photoaging process. Purple mangosteen is known to have abundant antioxidant properties such as xanthones and anthocyanins. This study aims to determine the effect of purple mangosteen peel extract on the collagen fiber in male Wistar rats after UV-B exposure.Methods: An experimental study was conducted among 21 male Wistar rats at Histology Laboratorium, Udayana University from a period of March-October 2017. The samples were divided into 3 groups as follows: control, placebo, and mangosteen extract with 7 rats in each group. Collagen fiber was assessed by using a light microscope with 400 times magnification. Statistical analysis was carried out using SPSS ver. 21 software using one way ANOVA.Results: The study found that percentage of collagen area within control group was 61.94%, placebo group 72.90%, and mangosteen peel extract 73.63%. The mean between-group analyzed using one way ANOVA found that there was a statistically significant difference in mangosteen peel extract than control group (p=0.0000), but not statistically significant if compared with placebo group (p=0.640) on the collagen fiber in male Wistar rats.Conclusion: there was a statistically significant difference in mangosteen peel extract than control group on the thickness of collagen fiber in male Wistar rats after UV-B exposure.